2011
DOI: 10.1371/journal.pone.0028335
|View full text |Cite|
|
Sign up to set email alerts
|

Schisandrin B Prevents Doxorubicin-Induced Chronic Cardiotoxicity and Enhances Its Anticancer Activity In Vivo

Abstract: BackgroundTo mitigate the cardiotoxicity of anthracycline antibiotics without compromising their anticancer activities is still an issue to be solved. We previously demonstrated that schisandrin B (Sch B) could protect against doxorubicin (Dox)-induced acute cardiotoxicity via enhancing cardiomyocytic glutathione redox cycling that could attenuate oxidative stress generated from Dox. In this study, we attempted to prove if Sch B could also protect against Dox-induced chronic cardiotoxicity, a more clinically r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 34 publications
4
29
0
1
Order By: Relevance
“…The results of the present study are in agreement with Xu [21] who showed weight loss, [22] who demonstrated significant reduction in systolic blood pressure [23] Different cellular mechanisms may explain doxorubicin-induced cardiac toxicity as increase intracellular iron accumulation causing increased oxidative stress [29], preventing the repair of damaged DNA strands [30], changes in vascular endothelium-derived vasoactive mediators (endothelin-1 and cardiac nitric oxide) [31] and alteration of cardiac-specific gene expression including struc tural, metabolic and enzyme activities [32].…”
Section: Discussionsupporting
confidence: 92%
“…The results of the present study are in agreement with Xu [21] who showed weight loss, [22] who demonstrated significant reduction in systolic blood pressure [23] Different cellular mechanisms may explain doxorubicin-induced cardiac toxicity as increase intracellular iron accumulation causing increased oxidative stress [29], preventing the repair of damaged DNA strands [30], changes in vascular endothelium-derived vasoactive mediators (endothelin-1 and cardiac nitric oxide) [31] and alteration of cardiac-specific gene expression including struc tural, metabolic and enzyme activities [32].…”
Section: Discussionsupporting
confidence: 92%
“…These results were also observed in several other antioxidant studies [7, 26]. Although the mechanism is still elusive, we speculate that it may be due to the functionally contradictory effects of some proteins critical for apoptotic signaling in different cell types induced by ATO, such as the proapoptotic effects of c-Jun-NH2-kinase (JNK) activation in ATO-induced ovarian cancer cells [27] in contrast to the antiapoptotic effects on JNK activation in some other cell lines [28, 29].…”
Section: Discussionsupporting
confidence: 89%
“…Excessive production of ROS is identified as a contributor to the damage of nuclear DNA, changes in calcium handling, restrain from cell survival and protein synthesis, disruption of sarcomere stability, and eventual cardiomyocyte death [32]. Due to their phenolic hydroxy structure, flavonoid compounds can act as strong natural antioxidants via combining directly with ROS and activating the antioxidant defense systems [33]. The present study was primarily designed to examine the potent protective effect of isorhamnetin on Dox-induced oxidative stress.…”
Section: Discussionmentioning
confidence: 99%